Beyond Resource Dependency: The Protective-Economy Model for Institutional Resilience in Faith-Based Enterprises - Mohammad, Majduddin; Kholis, Nur; Sa'dullah, M. Havy; Fahmi, Muhammad Izzul; Muhammad, Auwalu Shuaibu (El-Qist: Journal of Islamic Economics and Business (JIEB), 2026)
Prologue: Faith-based educational institutions increasingly face financial and environmental uncertainties that threaten their operational sustainability. Despite the growing role of Islamic social finance and community-based economic initiatives, limited empirical research explains how religious institutions develop integrated economic strategies to withstand systemic shocks. Objective: This study aims to conceptualize and empirically examine the protective economy as an institutional capability that strengthens resilience in faith-based organizations through the integration of Islamic social finance, circular economy practices, and strategic resource management. Methods: The research employs an embedded single-case study design at Pondok Pesantren Mambaus Sholihin, East Java, Indonesia. Data were collected through 34 semi-structured interviews, analysis of audited financial statements over a five-year period (2019–2025), and direct field observation. The data were analyzed using reflexive thematic analysis and fuzzy-set Qualitative Comparative Analysis (fsQCA) to identify causal configurations that support institutional resilience. Results/Findings: The findings demonstrate that the configuration of high income diversification, strong internal consumption loyalty, and adequate liquidity reserves enabled the institution to maintain uninterrupted service delivery during the COVID-19 pandemic and periods of commodity price volatility. Empirical indicators show that tuition dependence declined from 79% to 43%, liquidity reserves increased from 1.7 to 4.6 months of operational expenditure, waste-to-product conversion improved from 18% to 46%, and transparency scores rose from 72 to 88. Contribution: This study extends Resource Dependence Theory by highlighting the mediating roles of behavioral loyalty and governance transparency in strengthening resilience within faith-based organizations. It also proposes a protective economy dashboard—comprising the financial autonomy ratio, diversification index, waste-to-product ratio, and institutional trust score—as a practical monitoring framework for policymakers, philanthropic investors, and Islamic social finance institutions.